Trace fossils in a Lower Palaeozoic submarine canyon sequence — the Siegas Formation of northwestern New Brunswick, Canada - Pickerill, R. (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1981)
ABSTRACT The Siegat Formation (Silurian - early Llandovery) of northwestern New Brunswick represent*. In part, an ancient example of a aubmarlne canyon sequence, erosive Into and partially coeval with the Carye Ml11a Formation of lata Ordovician— middle Llandovery age. The canyon succession contains a moderately diverse ichno-fauna consisting of Buthotraphie, Chondritea, anguineu*, LfipliohniteB, Fuousopeia, Gordia arauata, Gordia, Gyrochorie, Belmintkoida labyrinthioa, tielminthopeia cf. obeli, Seonereitea bieerialie, Neonereitea unieerialie, Planolitee beverleyeneia, Prozopaleodictyon, Scalarituba mieeourieneie and Skolithoe. These trace fossils are described in detail. Contrary to previous prediction* that dwelling burrows and associated traces would predominate in submarine canyon sequences, the 5iegaa Formation contains traces produced essentially by vaglle sediment eaters. This ia perhaps bear explained by the absence within the canyon, at least for the majority of time, of sufficiently strong bottom currents, which precluded inhabitation by an active and abundant suspension feeding population- Instead, the sediments probably contained sufficiently abundant organic detritus to support an active population of lnfaunal sediment feeding organiama.